Traditional Knowledge and Ethnobotanical Utilization of Edible Plants in the Repong Damar Agroforestry System, Ngaras Subdistrict, Pesisir Barat Regency, Lampung, Indonesia - Sianipar, Naomi Putri Noverina; Duryat; Melya Riniarti; Ceng Asmarahaman (ICSIGER- International Conference on Science and Emerging Technology, 2025)
Ethnobotanical practices provide new insights into local wisdom and the well-preserved ecosystems found in Ngaras Subdistrict, Pesisir Barat Regency, Lampung. This knowledge reflects the close relationship between humans and their surrounding environment. The purpose of this study is to identify the continuity of ethnopharmacological practices, inventory the plant species utilized, and document the edible plant species used by local communities. The research employs an ethnographic approach, using data collection methods such as in-depth interviews, participatory observation, and documentation involving local people who possess traditional knowledge of plant utilization within the repong damar system. Informants were selected using the snowball sampling technique to reach relevant sources such as repong managers, traditional leaders, and local residents directly involved in the use of biological resources. The findings reveal that the community utilizes various plant species as sources of food, including Lansium domesticum (duku), Durio zibethinus (durian), Archidendron pauciflorum (jengkol), Parkia speciosa (petai), Garcinia mangostana (mangosteen), Gnetum gnemon (melinjo), Cocos nucifera (kelapa), Areca catechu (pinang), Etlingera elatior (kecombrang), Archidendron bubalinum (jaling), Syzygium aqueum (jambu air), Artocarpus integer (cempedak), and Rubus rosifolius (arbei). Most of these species are used for personal consumption, while others serve as additional sources of income for the local community. The utilization practices remain rooted in local wisdom, emphasizing sustainability and ecological balance. This study particularly focuses on the food sector, aiming to understand and document how the community in Ngaras Subdistrict, Pesisir Barat Regency, utilizes the diversity of edible plants found within the repong damar ecosystem. Through the ethnographic approach, the research explores traditional knowledge related to edible plant species, methods of processing, and their roles in daily life. Overall, the study highlights that the diversity of edible plants in the repong damar plays a vital role in supporting food security and community welfare. Through documentation and ethnobotanical analysis, this research seeks to preserve traditional knowledge passed down through generations, serving as a foundation for future efforts in the sustainable management and conservation of biological resources.